2012
DOI: 10.3201/eid1809.120431
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 Virus among Healthy Show Pigs, United States

Abstract: Because animals can transmit some diseases to people, it is wise to be cautious around animals that carry these diseases. But how do you know which animals are carrying disease? Sometimes they appear perfectly healthy. A study of 57 apparently healthy show pigs at a 2009 US state fair found that almost 20% were carrying influenza virus and at least 4 were carrying the 2009 pandemic virus. Of concern is the possibility that different types of influenza virus—pandemic, swine, avian—could combine in pigs and emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
2
33
0
1
Order By: Relevance
“…2010, Song et al 2010, Forgie et al 2011, CDC 2012, Gray et al 2012, Williamson et al 2012). Swine workers and their family members are at increased risk of contracting swine influenza virus infections ( Olsen et al 2002, Myers et al 2006, Gray et al 2007, Robinson et al 2007, Yassine et al 2009, Beaudoin et al 2012, CDC 2012, Wong et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2010, Song et al 2010, Forgie et al 2011, CDC 2012, Gray et al 2012, Williamson et al 2012). Swine workers and their family members are at increased risk of contracting swine influenza virus infections ( Olsen et al 2002, Myers et al 2006, Gray et al 2007, Robinson et al 2007, Yassine et al 2009, Beaudoin et al 2012, CDC 2012, Wong et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…15 Genomic analysis of viral isolates from exhibition pigs compared with human isolates confirmed zoonotic transmission. 21 Exhibition swine infected with IAV often do not show clinical signs of illness, [21][22][23] indicating the need for direct diagnostic tests.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies suggesting that multiple subtypes of influenza viruses, including A(H1N1)pdm09, are infecting dogs (6)(7)(8)(9)(12)(13)(14). It has also been shown that dog-to-dog transmission of A(H1N1)pdm09 can occur but with low infection rates (9).…”
mentioning
confidence: 99%
“…Since then, it has continued to circulate among humans, along with a number of other seasonal influenza viruses. The influenza A(H1N1)pdm09 virus has also been detected in a number of nonhuman species, including pigs, poultry, dogs, and cats (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%